Our clinical results in the management of proximal humeral fractures - Eriten, Semih; Demir, Sukru; Emeli, Adem; Altunkılıç, Tarık; Sevimli, Doç. Dr. Reşit; Önce, Gökhan (My University, 2020)
Aim: The aim of this study was to evaluate the clinical, radiological and functional results of patients treated with different methodsin our clinic for proximal humerus fracture.Material and Methods: A total of 106 patients with a diagnosis of proximal humerus fracture, who were scheduled for treatment,received management and followed up periodically after discharge were included. Patient files, X-RAY radiographs in the PACSsystem, surgical notes and outpatient epicrisis were used. Functional results were evaluated according to Constant shoulder scoreat the last visit.Results: The mean age of the patients was 53.6 years (17-94). The mean follow-up period was 11.3 months (6-40 months). 55 (51.9%)had Type II, 35 (33%) had Type III and 16 (15.1%) had Type IV proximal end humeral fractures. As a result of the evaluation performedat the last follow-up of the patients, Constant-Murley’s total score was 64.50 out of 100 (31-88). Score distribution according to Neerclassification of patients; A Constant-Murley score median with a Neer Type II fracture was 74.00 (36-88), a Constant-Murley Score medianwith a Neer Type III fracture was 61.00 (31-78), and a Constant-Murley score median with a Neer Type IV fracture was 44.50 (33-70).Conclusion: When the fracture type and functional outcome of the patients were compared, functional outcome decreased as thefracture type increased. Young patients had better functional results than older patients.
Keywords: Genel ve Dahili Tıp; Sağlık Bilimleri ve Hizmetleri; Cerrahi; Ortopedi